John Forbes (1799–1823) in Mozambique: itineraries, dates, and plant collections - Figueiredo, Estrela; Smith, Gideon F. (Phytotaxa, 2025)
The British expedition that lasted from 1822 to 1826 and was led by Capt. William Fitz William Owen was charged with surveying, mapping, and charting parts of, inter alia, the southern and eastern coasts of Africa. It had an additional mandate: to obtain natural history objects and artefacts, and for this purpose John Forbes (1799–1823) was appointed as the first (and at the time, only) collector. From September 1822 to August 1823, Forbes made numerous biological collections in Mozambique, in southeastern Africa. His collecting localities and numbers in that country, which have often been wrongly cited and confused in the literature, are discussed in this paper. Because most of his field book records survived and are extant, we determined that during the time that Forbes spent in Mozambique, he made at least 226 plant collections. Forbes died in August 1823 during an expedition up the Zambezi River. All the collections, their metadata, and other associated records that he made in Mozambique after 14 March 1823 were lost upon his death. The Forbes collections that are either cited in the literature or have been located in herbaria belong to 144 taxa, with only 83 of these taxa having specimens databased and (mostly) imaged. For 42 of the taxa, specimens collected by Forbes became the types of names; 47 of these specimens, i.e., including duplicates, have been located. Forbes’s collections are mostly unnumbered and labelled with scant information and are sometimes mislabelled. Following a comparison between the Forbes specimens and his field notes, information on his exsiccata is corrected. For several collections, the collecting number, date, and locality are confirmed, or are posited here, and guidance is provided on how the specimens should be cited. The whereabouts of the majority of Forbes’s specimens remain unknown.